Manufacturing environment and economic growth in South Africa: evidence from Fourier Toda Yamamoto causality test. (26th February 2020) - Saliminezhad, Andisheh; Bahramian, Pejman
This study aims to bring into account the dynamic impact of business constraints in the manufacturing sector on economic growth for South Africa during the period 1987-2016. To this end, we use the so-called manufacturing environment index, and we perform a causality analysis through the application of the conventional Toda-Yamamoto method. However, we have shown that the data encompasses the structural breaks. Hence, the standard causality test is prone to misspecifications. Thereby, we apply the newly Fourier Toda-Yamamoto method which accounts for structural shifts in a causality analysis. In contrast to the no evidence of causation detected using the traditional approach, the results of Fourier Toda-Yamamoto suggest a unidirectional Granger causality running from manufacturing environment index to economic growth. Our findings highlight the importance of survey indicators in the assessment of economic development policies. Moreover, it emphasises on covering the possible structural breaks to deliver more reliable inference.